Radiocarbon calibration: from bane to blessing - Bronk Ramsey, C (Cambridge University Press, 2023)
Temporal and spatial variation in radiocarbon (14C) in the atmosphere has been the subject of investigation from the first pioneering work of Libby and Arnold. However, as the precision of measurements has improved, now by almost two orders of magnitude, what constitutes a significant variation has also changed. Furthermore, it has become possible to test degrees of variation over much longer timescales and with ever wider geographic coverage. As knowledge has improved, the interpretation of 14C measurements has had to be revised. These re-evaluations, and the loss of chronological precision that comes with accurate calibration, have often been seen as an unfortunate drawback in the 14C dating method. However, these problems have stimulated extensive research in global 14C records, statistical methods for dealing with complex 14C data, and measurement methods. This research has provided a wealth of information useful for other scientific challenges, most notably the quantification of the global carbon cycle, but also enabled, in the right circumstances, measurement precision an order of magnitude better than if there had been no variation in atmospheric 14C. Challenges remain but the research undertaken for 14C calibration has, through its ingenuity and innovation, provided rich scientific dividends in both chronology and broader geoscience.